Standing Army - Parenti, Enrico; Fazi, Thomas (Italy, 2010)
Over the course of the last century, the U.S. has encircled the world with a web of military bases unlike any other in history. Today, they amount to more than 700, in 40 countries. No continent is spared. This documentary sheds light on one of the most defining and less-known realities of our time, through eye-opening interviews and testimonies.
Verzio Film Festival Submission
Keywords: Documentary films